Analisis Integrasi Spasial Pasar Cabai Merah di Provinsi Sumatera Utara - Warsito, Edy Warsito; Chalil, Diana; Lindawati (Universitas Medan Area, 2025)
North Sumatra Province is one of the largest red chili producing provinces in Indonesia. Red Chili production is spread across several districts and meets the needs of markets in North Sumatra. Production and differences in distance between producer areas and markets affect prices at the consumer level. Fluctuations in the price of Red Chili often occur so that this commodity is one of the contributors to inflation in North Sumatra. Inflation is measured from price indicators in 5 cities, namely Medan, Pematang Siantar, Sibolga, Padangsidimpuan, and Gunungsitoli. The purpose of this study was to determine the development of Red Chili production and prices and to analyze the integration of prices between Red Chili producer markets in 5 (five) cities in North Sumatra Province. The benefits of this study are as information for the North Sumatra Provincial Government in making policies. This study uses the descriptive analysis method and the Vector Error Correction Model (VECM) method from weekly data for a period of 3 years, namely the period 2021 to 2023. The results of the study show that the comparison between production and demand for Red Chili in North Sumatra is in a surplus condition. Prices between the Red Chili producer markets in Medan City, Pematang Siantar City, Padang Sidempuan City, Sibolga City and Gunung Sitoli City are perfectly integrated. There is a short term relationship between the price of red chilies in Medan and Gunung Sitoli, Pematang Siantar and Sibolga. Price of red chilies in Padang Sidempuan with Sibolga, Medan and Pematang Siantar. There is a long-term relationship between the price of red chilies in Gunung Sitoli and Medan, Padang Sidempuan, Pematang Siantar and Sibolga. The relationship that occurs between the red chili price variable is a causal relationship, indicating that there is one-way causality between the red chili price variable in Medan and the price of Pematang Siantar chili and the price of Sibolga chili.